Urban Thermal Comfort and Microclimate Design in Public Open Spaces for Social Activities: A Literature Review with Implications for Palembang City, Indonesia - Liya Isma Rahmaniya; Karina Karina (Journal of Architectural Design and Urbanism, 2026)
This study presents a structured literature review examining the relationship between urban thermal comfort, microclimate-responsive design, and social activities in public open spaces within tropical cities, with implications for Palembang City, Indonesia. The review synthesizes 31 peer-reviewed journal articles published between 2014 and 2025 retrieved from Scopus, Web of Science, ScienceDirect, and Google Scholar databases. The study applies thematic synthesis to identify dominant microclimatic variables, methodological approaches, and research gaps related to outdoor thermal comfort and public-space use. This paper aims to review and synthesise existing research on urban thermal comfort and microclimate design in outdoor public spaces, with a particular focus on their relationship to social activities, to develop a conceptual framework relevant to Palembang’s urban context. The findings indicate that shading strategies, vegetation composition, surface materials, and spatial configuration are key factors influencing perceived thermal comfort and levels of social engagement. Design elements such as tree canopy density, high-albedo surfaces, and appropriate space orientation are shown to reduce heat stress and encourage longer duration and greater intensity of social activities in hot-humid environments. This review highlights the importance of integrating microclimate sensitive design principles into urban planning policies and public open space development to promote thermally comfortable and socially active urban environments in tropical cities.